(3MGTjI Ydi cJGH aj Gdabg GdTGaYjs - (3eLghds
(3ChdgG (B:s
(3GSJOQGc Ydi bhdg adG JHdd bhdg HYO hLhO GdeGA heYOdG bHdg Ydi eG GYJeOg GdQedj hYfO GHf MLQ Cf GdeYjI edMbI HGdbHdjIs
(3BNQgG (B:s
(3bhdg eQHYI GdN HNdGa VjbI GdQCS ML bhdg aEMdGbj dgG Cj dCfg jajO Cf eKd GdeQHYI GdeOhQIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3Gdabg GdTGaYjs